Brain norepinephrine identified by mass spectrometry is associated with reproductive status of females of the linden bug Pyrrhocoris apterus - Chvalova, Daniela; Zdechovanova, Lenka; Vaneckova, Hana; Hodkova, Magdalena (Comparative biochemistry and physiology. Part B, Biochemistry & molecular biology, 2014)
Several biogenic amines, including controversial presence of norepinephrine (NE), were identified by the high performance liquid chromatography equipped with electrospray ionisation mass spectrometry in brain complexes of adult females of Pyrrhocoris apterus. Quantitative analysis was performed by the high performance liquid chromatography coupled to electrochemical detector. Levels of NE, dopamine (DA), octopamine (OA) and 5-hydroxytryptamine (5-HT) in brain complexes were measured in reproductive vs. diapause females. In field collected samples, levels of NE and DA were significantly higher in reproductive (May) than in non-reproductive (Sep, Oct, Feb) females. In laboratory females, NE is higher in long day photoperiod (reproduction) than in short day photoperiod (diapause) already from the first week of the adult age, while DA shows differences between the two contrasting photoperiods only from the second week of the adult age. No association between reproductive status and levels of OA and 5-HT was found.
Keywords: Brain complex; Octopamine; Chromatography, Liquid; Catecholamines; Brain; Reproduction; oktopamin; noradrenalin; Norepinephrine; Tilia; dopamin; chromatografie kapalinová; rozmnožování; Dopamine; katecholaminy; Animals; ženské pohlaví; roční období; Seasons; Spectrometry, Mass, Electrospray Ionization; zvířata; Mass spectrometry; Adult diapause; mozek; hmotnostní spektrometrie s elektrosprejovou ionizací; Female; Heteroptera; Insects